The Oxford guide to the United States Government - Patrick, John J. 1935-; Pious, Richard M. 1944-; Ritchie, Donald A. 1945- (Oxford Univ. Press, 2001)
"The Oxford Guide to the United States Government is the ultimate resource for authoritative information on the U.S. Presidency, Congress, and Supreme Court, and other federal government agencies. Written by three top scholars, its pages brim with the key figures, events, and structures that have animated U.S. government for more than 200 years." "In addition to coverage of the 2000 Presidential election, this Guide features biographies of all the Presidents, Vice Presidents, and Supreme Court justices, as well as notable members of Congress, including current leadership; historical commentary on past elections, major Presidential decisions, international and domestic programs, and the key advisors and agencies of the executive branch; in-depth analysis of Congressional leadership and committees, agencies and staff, and historic legislation; and detailed discussions of 100 landmark Supreme Court cases and the major issues facing the Court today. In addition to entries that define legal terms and phrases and others that elaborate on the wide array of government traditions, this valuable book includes extensive back matter, including tables of Presidential election results; lists of Presidents, Vice Presidents, Congresses, and Supreme Court Justices with dates of service; lists of Presidential museums, libraries, and historic sites; relevant web sites; and information on visiting the White House, the Capitol, and the Supreme Court building." "A one-stop, comprehensive guide that will assist students, educators, and anyone curious about the inner workings of government, The Oxford Guide to the United States Government will be a valued addition to any home library."--BOOK JACKET.